Analisis Sintaksis: Fungsi, Kategori, dan Peran Pada Berita Detik.com - Septiani, Alika Dwi; Maheltra, Alma Neysa; Heryanti, Denia; Adawiyah, Sulis Najahul; Suherman, Syahira Mawla; Lisnawati, Iis (Universitas Pahlawan Tuanku Tambusai, 2025)
Language as the main communication tool has a complex structure, one of which can be studied through syntax, namely the study of word order in forming sentences. This study aims to describe the sentence structure, function, category, and role of syntax in the Detik.com news text entitled